2017
DOI: 10.20886/jphh.2017.35.4.273-288
|View full text |Cite
|
Sign up to set email alerts
|

Kerusakan Tegakan Tinggal Akibat Pemanenan Kayu Pada Hutan Tropis Berbukit Di Kalimantan Tengah

Abstract: One indicator of sustainable forest management is the minimum impact of residual stand damage caused by timber harvesting activities. This paper examines stand damage due to timber harvesting on hilly tropical forest, Central ABSTRAKSalah satu indikator pengelolaan hutan lestari adalah adanya dampak kerusakan tegakan tinggal yang ditimbulkan oleh kegiatan pemanenan kayu. Tulisan ini mempelajari kerusakan tegakan tinggal akibat pemanenan kayu di hutan tropis berbukit di Kalimantan Tengah. Pengamatan dilakukan d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
3
Order By: Relevance
“…Other studies on Indonesia's tropical forests also showed similar damages suffered by the residual stands. (Soenarno et al, 2017) reported that broken stem was the dominant damage type (56.37%) that occurred due to felling activity in a tropical natural forest of Central Kalimantan. Furthermore, (Matangaran et al, 2019) reported that broken stem and crown injuries were the dominant damage types that occurred due to logging in the tropical forests of Central Kalimantan and West Sumatra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on Indonesia's tropical forests also showed similar damages suffered by the residual stands. (Soenarno et al, 2017) reported that broken stem was the dominant damage type (56.37%) that occurred due to felling activity in a tropical natural forest of Central Kalimantan. Furthermore, (Matangaran et al, 2019) reported that broken stem and crown injuries were the dominant damage types that occurred due to logging in the tropical forests of Central Kalimantan and West Sumatra.…”
Section: Resultsmentioning
confidence: 99%
“…Timber felling activity in this study was conducted by a chainsaw operator who has three years of experience in natural forest timber logging. Previously, the operator Figure 2 Design of observation sample plots in the logging compartment (Soenarno et al, 2017 worked as a chainsaw operator in oil palm plantations. This operator also never attended RIL training.…”
Section: Study Areamentioning
confidence: 99%
“…Akibatnya volume kayu batang bebas cabang (BBC) yang dimanfaatkan tidak maksimal, terjadinya limbah pemanenan kayu, dan kerusakan tegakan tinggal. Besarnya volume limbah pemanenan kayu berkisar antara 12−25% (Idris, Dulsalam, Soenarno, & Sukanda, 2012;, dan menimbulkan kerusakan tegakan tinggal berkisar antara 17−40% (Elias, 2016;Eroǧlu, Öztürk, Sönmez, Tilki, & Akkuzu, 2009;Muhdi, Elias, Murdiyarso, & Matangaran, 2014;Soenarno, Endom, & Bustomi, 2017). Menurut Garldan dan Jackson (1997) dan Uusitalo, Kokko, dan Kivin (2004), dalam pemanenan hutan, penebangan, dan bucking yang benar akan meningkatkan efisiensi, kualitas kayu, dan pendapatan dari hasil penjualan kayu.…”
Section: Pendahuluan Iunclassified
“…Some difficulties faced by Indonesia Forest Company (Perhutani) when facing more and more, forest village farmers are destroying forests causing tension in Indonesia Forest Company (Perhutani) relations with forest villagers. Destruction is mainly caused by pressure from the surrounding community which is related to poverty, thus overcoming it by overcoming the problem of poverty [1], [8], [9], [10]. To prevent forest destruction is to empower the economic life of forest village communities [5], [11], [12].…”
Section: The Countermeasure Of Forest Destructionmentioning
confidence: 99%